2007
DOI: 10.1126/stke.4042007pe52
|View full text |Cite
|
Sign up to set email alerts
|

β-Actin: A Regulator of NOS-3

Abstract: Beta-actin is traditionally considered a structural protein that organizes and maintains the shape of nonmuscle cells, although data now indicate that beta-actin is also a signaling molecule. beta-actin is directly associated with nitric oxide synthase type 3 (NOS-3) in endothelial cells and platelets, and this interaction increases NOS-3 activity and the affinity of NOS-3 for heat shock protein 90 kD (Hsp90). The beta-actin-induced increase in NOS-3 activity may be caused directly by beta-actin, the binding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Single-locus analysis suggested a positive association of the G allele of rs8066114 and the T allele of rs4461142 with HAPE under the dominant model of inheritance. Although no significant associations were found for any of the other four polymorphisms, their corre- (Ahsan et al 2006;Su et al 2007), which may lead to HAPE. Although the association between NOS3 gene variants and HAPE susceptibility has been previously assessed in a number of studies, the results have not been consistent, especially for the NOS3 rs1799983 (G894T) polymorphism (Droma et al 2002;Weiss et al 2003;Ahsan et al 2004Ahsan et al , 2006Sun et al 2010).…”
Section: Discussionmentioning
confidence: 84%
“…Single-locus analysis suggested a positive association of the G allele of rs8066114 and the T allele of rs4461142 with HAPE under the dominant model of inheritance. Although no significant associations were found for any of the other four polymorphisms, their corre- (Ahsan et al 2006;Su et al 2007), which may lead to HAPE. Although the association between NOS3 gene variants and HAPE susceptibility has been previously assessed in a number of studies, the results have not been consistent, especially for the NOS3 rs1799983 (G894T) polymorphism (Droma et al 2002;Weiss et al 2003;Ahsan et al 2004Ahsan et al , 2006Sun et al 2010).…”
Section: Discussionmentioning
confidence: 84%
“…We have reported that the ␤-actin-binding site on eNOS protein is located at the oxygenase domain (6,7). The oxygenase domain is involved with superoxide generation when eNOS is eNOS-␤-Actin Interaction FEBRUARY 12, 2010 • VOLUME 285 • NUMBER 7…”
Section: An Increase In No Production Induced By ␤-Actin Binding To Ementioning
confidence: 99%
“…The synthesis of NO requires NADPH, tetrahydrobiopterin (BH 4 ), flavin adenine dinucleotide (FAD), flavin mononucleotide (FMN), and O 2 as cofactors and results in NO and the co-product L-citrulline (1). eNOS is tightly regulated by transcriptional, post-transcriptional, and post-translational mechanisms (5,6). Protein-protein interactions represent an important post-translational mechanism for eNOS regulation (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The triggering of endothelial signaling by mechanic forces seems to be mostly determined by the cytoskeleton, which represents a highly dynamic network that constantly assembles and disassembles, playing an active role in responding to mechanical stimuli (Wong et al, 1983). The cytoskeleton rearranges upon changes on stress and stretch and activates signaling molecules, such as NO production, that are capable to regulate vascular tone in order to keep homeostasis (Su et al, 2005;Su et al, 2007). An increase in arterial wall stiffening by aging could alter the impact of a mechanical stimulus, and therefore induce a significant reduction or dysfunction in the signaling pathways activated by shear stress (Kliche et al, 2011).…”
Section: Effects Of Aging On Vascular Functionmentioning
confidence: 99%